Mental health issues and psychological factors in athletes: detection, management, effect on performance and prevention: American Medical Society for Sports Medicine position statement - Executive summary - Chang, C.; Putukian, M.; Aerni, G.; Diamond, A.; Hong, G.; Ingram, Y.; Reardon, C. L.; Wolanin, A. (British Journal of Sports Medicine, 2020)
The American Medical Society for Sports Medicine convened a panel of experts to provide an evidence-based, best practices document to assist sports medicine physicians and other members of the athletic care network with the detection, treatment and prevention of mental health issues in competitive athletes. This statement discusses how members of the sports medicine team, including team physicians, athletic trainers and mental health providers, work together in providing comprehensive psychological care to athletes. It specifically addresses psychological factors in athletes including personality issues and the psychological response to injury and illness. The statement also examines the athletic culture and environmental factors that commonly impact mental health, including sexuality and gender issues, hazing, bullying, sexual misconduct and transition from sport. Specific mental health disorders in athletes, such as eating disorders/disordered eating, depression and suicide, anxiety and stress, overtraining, sleep disorders and attention-deficit/hyperactivity disorder, are reviewed with a focus on detection, management, the effect on performance and prevention. This document uses the Strength of Recommendation Taxonomy to grade level of evidence.